Influence of the carbohydrate fragment position in the macrocycle of chlorine e6 trimethyl ester glycosylated derivatives on their in vitro photo- induced activity - R. I. Yakubovskaya; A. D. Plyutinskaya; E. A. Plotnikova; M. A. Grin; A. F. Mironov; V. S. Sergeeva (Biomedical Photonics, 2014)
The physicochemical and photophysical properties, as well as photo-induced activity, of glycoconjugates based on chlorine е6 trimethyl ether with various positions of carbohydrate fragment in the macrocycle have been studied. The photo-induced activity was investigated in the human (HEp2, A549 and HT29) and animal (LLC) cell lines. The tested compounds showed in vitro both high photo-induced activity and high stability in the dark. The photosensitizer with galactose in the A pirrole ring demonstrated the highest activity (the half maximal inhibitory concentration (ИК50) varied from 27±2 nM to 75±5 nM in tests on different cell lines). Dyes with sugar substitutes in the C pirrole ring were 5–10 times less active.